2014
DOI: 10.2118/160189-pa
|View full text |Cite
|
Sign up to set email alerts
|

The Value of Assessing Uncertainty

Abstract: Despite the perception of lucrative earnings in the oil industry, various authors have noted that industry performance is routinely below expectations. For example, the average reported return for the industry was around 7% in the 1990s, even though a typical project hurdle rate was at least 15%. The underperformance is generally attributed to poor project evaluation and selection due to chronic bias. While a number of authors have investigated cognitive biases in oil and gas project evaluation, there have bee… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
3
0
2

Year Published

2014
2014
2019
2019

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 23 publications
(5 citation statements)
references
References 38 publications
0
3
0
2
Order By: Relevance
“…Unfortunately, humans are poor at assessing uncertainty, i.e., we are biased. Several authors have reported on the tendency for overconfidence and optimism in the petroleum industry (Capen 1976;Welsh et al 2005;McVay and Dossary 2014).…”
Section: Statement and Significance Of The Problemmentioning
confidence: 99%
“…Unfortunately, humans are poor at assessing uncertainty, i.e., we are biased. Several authors have reported on the tendency for overconfidence and optimism in the petroleum industry (Capen 1976;Welsh et al 2005;McVay and Dossary 2014).…”
Section: Statement and Significance Of The Problemmentioning
confidence: 99%
“…According to McVay and Dossary (2014), even moderate overconfidence and optimism can lead to portfolio disappointment of more than 30%. It is also important to evaluate reserves and resources early for optimal development.…”
Section: Statement and Significance Of The Problemmentioning
confidence: 99%
“…Otro factor de mayor relevancia ha sido: la falta de pruebas claras de que el incremento de la cuantificación de la incertidumbre y del análisis de decisiones, haya conducido a una mejora significativa en la toma de decisiones y en el rendimiento en la industria. Cabe resaltar, que la mayoría de los beneficios que se citan en los procesos de cuantificación realmente son de naturaleza cualitativa, motivo por el cual muchas empresas son reacias a adoptar estos procesos [6].…”
Section: Tabla 1 Bases De Datos De Centros Pobladosunclassified
“…Basado en la fórmula de la media aritmética ponderada, tenemos: W = (I1 + I2 + I3) / (I1 x P + I2 x P + I3 x P) (6) dónde: I1 = Índice de Confiablidad de la Precisión de la Coordenadas Proyectadas. I2 = Índice de Confiablidad de la Georreferenciación.…”
Section: Precisión De Equipo Y Asignación De Pesosunclassified